Some Behavior of Coarse structure and Coarse equivalence - Kajan, N.; Kannan, K. (Advances in Mathematics: Scientific Journal 9, 2020)
I am going to introduce some properties of coarse structure. Coarse space is defined for large scale in metric space similar to the tools provided by topology for analyzing behavior at small distance, as topological property can be defined entirely in terms of open sets. Analogously a large scale property can be defined entirely in terms of controlled sets. The properties we required were that the maps were coarse (proper and bornologous), but why do these maps imply that the spaces have the same large structure? Essentially this has to do with contractibility. Spaces which are the same on a large scale can be scaled so that the points are not too far away from each other, but we are not concerned with any differences on small scale that may arise. In addition I am going to explain some basic definition related with the title of my research work besides ,I want to investigate several results in coarse map, coarse equivalent and coarse embedding. Further I have to proof some results of product of coarse structure. Coarse map need not be a continuous map. Coarse space has some applica tion in various parts in mathematics. More over coarse structure is a large scale property so we can invest some results related with coarse space and topology. Topology is the small scale structure, but topological coarse structure is the large scale structure. We investigated some results about coarse maps, coarse equivalent and coarse embedding.